IMPLEMENTATION OF RISK ASSESSMENT AT PT AMEERA HATI MULIA - Noriska, Ni Komang Septia; Cindy Untari; Yohanes Wien Tineka (Jurnal Manajemen Bisnis dan Terapan, 2025)
Risk cannot be avoided in a business; the uncertain nature allows companies to conduct risk assessments in each division. The risk management assessment process includes risk identification, risk analysis, and risk evaluation. This research was conducted to determine and analyze the implementation of risk management assessment at PT Ameera Hati Mulia. This research uses primary and secondary data types and sources. Primary data, in the form of interview results and secondary data, includes company profiles and a recap of the number of Umrah pilgrims registered. The data collection methods used are interviews, observation, and documentation. The method of discussion in this study is a qualitative descriptive discussion. In this study, researchers researched and assessed the risks in the Umrah and Hajj plus bureau company PT Ameera Hati Mulia. The risk assessment includes risk identification, analysis, and evaluation processes. Based on the results of research conducted by the author, several risks have occurred at PT Ameera, including operational and marketing risks. This research shows two types of risks at PT Ameera Hati Mulia: operational risk and marketing risk. A risk assessment is important to help the company anticipate vulnerabilities. PT Ameera ensures that any impacts arising from risks can be overcome and immediately seeks solutions if a risk event occurs. Suggestions that the author can convey based on the results of this study: PT Ameera Hati Mulia needs to create a risk register table that is useful for identifying possible risks that can occur in the company, as well as preventing and dealing with these risks.